COMMANDITER FELLOWSHIP IN COMMERCIAL LAW - Prasasti Dyah Nugraheni (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2020)
Economic activity in the country of Indonesia experienced very rapid development. This can cause the emergence of a problem that exists in the community. Vice versa, a legal entity in carrying out its business activities also requires money. One of the business entities is Commander Association. A Commander Association is a form of business that is not a legal entity. A Commander Association in carrying out its business activities gets capital through loans from banking institutions and from non-banking institutions with a certain guarantee. This journal is written using a normative juridical method because this journal uses secondary data that is used as a tool to collect data. Therefore, the journal that is written will explain about a Commissioner Alliance in commercial law. The main problem in this journal is more focused on explaining the meaning of business entity, forms of business entity, understanding of Communist Alliance, process of establishing Communist Fellowship, responsibility of allied parties of Commander Association, forms of Commander Association, legal status of Commissioner Alliance, and dissolution process of Commissioner Alliance. This is because there is no legal rule that specifically regulates a form of business entity in the form of the Commander Association.